Efficient PID Controller based Hexapod Wall Following Robot - Hendril Satrian Purnama; Tole Sutikno; Nuryono Satya Widodo; Srinivasan Alavandar (IAES Indonesia Section, 2019)
This paper presents a design of wall followingbehaviour for hexapod robot based on PID controller. PIDcontroller is proposed here because of its ability to controlmany cases of non-linear systems. In this case, we proposed aPID controller to improve the speed and stability of hexapodrobot movement while following the wall. In this paper, PIDcontroller is used to control the robot legs, by adjusting thevalue of swing angle during forward or backward movement tomaintain the distance between the robot and the wall. Theexperimental result was verified by implementing the proposedcontrol method into actual prototype of hexapod robot.